A Study Focused On China’s Heihe River Basin Using Quantitative Remote Sensing To Study Ecohydrology In Water-Scarce Habitats - Hongmei, Xu; Al-Odaini, Aiman (International Journal of Membrane Science and Technology, 2023)
Ecohydrology is the study of how ecosystems and the water cycle are impacted by the movement of water. Ecohydrology examines the natural effects of water flow. No text is available for researchers to input. In order to manage water resources in an ecohydrological way, it is necessary to understand and measure the relationship between plants & water. Because there isn't enough water, dryland watershed management is still a problem. If valid correlations can be found, indications of water demand may be derived from groundwater recharge, drainage, hydraulic factors, and changes in vegetation. In arid areas, the impact of vegetation for groundwater circulation has been the subject of several remote sensing studies. Surface flow and groundwater recharge predictions may be better made using vegetation mapping than with surface and subsurface sampling and analysis. Ecohydrological models and techniques, including remote sensing, are necessary for predicting a plant's response to changes in water intake & flow. By improving satellite surveillance, researchers may be able to learn how plants respond to changes in water levels. Ecohydrological processes can only be understood with the use of hydrology and remote sensing.